فاعلية التدريس عن بعد باستخدام المنصات التعليمية من وجهة نظر معلمي التربية الإسلامية في محافظة شمال الباطنة بسلطنة عمان: The Effectiveness of Distance Teaching Using Educational Platforms from the Point of View of Islamic Education Teachers in the Governorate of North Al Batinah in the Sultanate of Oman - Al Zadjali, Maymoona Darwish; Al Kaabi, Suleiman Muhammad; Al Shibli, Samira Khamis (Journal of Islamic Educational Research, 2023)
This study aimed to identify the effectiveness of teaching using educational platforms from the point of view of Islamic education teachers in the Sultanate of Oman. To achieve the aim of the study, the researchers adopted the descriptive approach. A questionnaire was designed using Google Forms and distributed electronically to the study sample of male and female Islamic education teachers; In its final form, after verifying its validity and stability, it consisted of (23) phrases. The study sample consisted of (348) male and female teachers of Islamic education in the second cycle of basic and post-basic education for the year 2020/2021 AD, who were selected in a simple random way with a percentage of (55.7%) of the study population. After collecting and analysing data statistically using the SPSS program, the study concluded a number of results, represented in the following: The effectiveness of using educational platforms in distance education in light of the pandemic from the point of view of Islamic education teachers is great. And there were no statistically significant differences at the level (α ≤ 0.05) in the effectiveness of using educational platforms in education according to the responses of Islamic education teachers due to gender variables (male-female). and practical experience they have. In light of the findings of the study, it recommended the continuation of the use of educational platforms in the educational process, and the design of some Islamic education lessons to be taught in the distance learning system after the end of the pandemic (Covid-19).